International Marketing Diversification: A Path to Sustainable Enterprise Development - Tanasiichuk, Alona; Dybchuk, Liudmyla; Shevchuk, Anna; Hromova, Olha; Mykhailo, Havenko; Zakharchuk, Iryna; Ulianych, Yuliia (European Journal of Sustainable Development, 2025)
This study demonstrates the critical importance of international marketing diversification during wartime, particularly for Ukrainian businesses seeking to expand their sales markets and mitigate risks associated with specific markets. By adopting this strategy, businesses can better withstand conflict-induced challenges and remain resilient in difficult circumstances. The article explores strategies for international marketing diversification that can help companies maintain competitiveness during wartime conditions. Drawing on a synthesis of domestic and international scholarly perspectives, the study positions international marketing diversification as a forward-looking approach to securing enterprises